THIONAMIDE-ASSOCIATED NECROTIZING AUTOIMMUNE MYOPATHY (NAM) IN GRAVES’ DISEASE: A CASE REPORT - Thewjitcharoen, Yotsapon; Chatchomchuan, Waralee; Porramatikul, Sriurai; Anukoolwittaya, Prakit; Rajatanavin, Rajata; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Necrotizing Autoimmune Myopathy (NAM) has never been reported as a cause of myositis in thionamide-treated Graves’ disease (GD). A 21-year-old Thai female presented with a 12-month history of palpitations. A diagnosis of GD was confirmed by elevated serum anti-TSH receptor antibody. Methimazole (MMI) 20 mg/day was started. Eleven weeks after therapy, she complained of generalized muscle pain. Elevated serum CK level at 791 U/L (<170) was found. MMI was switched to Propylthiouracil (PTU) 450 mg/day but serum CK level further rose to 2,538 U/L with worsening myalgia. Radioactive iodine (RAI) 30 mCi was given and she developed hypothyroidism at 9 weeks after treatment. She unexpectedly developed rhabdomyolysis (peak serum CK level at 13,084 U/L) while having a mild COVID-19 infection at 10 weeks after RAI. Finally, the diagnosis of NAM was established based on muscle biopsy. Our case highlighted NAM as an unusual cause of thionamide-associated myositis.